Aspirin desensitization in nonsteroidal anti-inflammatory exacerbated respiratory disease: The first prospective cohort in Chile - Siña, María Josefina; Valdés, Felipe; Zelada, Úrsula; Tagle, María Teresa; Campillay, Rolando; Sandoval, Daniela; Herrera, Pablo; Bastías, Carla (Frontiers in Allergy, 2023)
Background: Non-steroidal anti-inflammatory exacerbated respiratory disease (N-ERD) is characterized by the Samter triad: chronic rhinosinusitis with nasal polyps, asthma and non allergic hypersensitivity to NSAIDs. Its diagnosis is based on a complete clinical history and aspirin (ASA) challenge test. Medical treatments include biological drugs and ASA desensitization. Objective: Evaluate the clinical response of patients with N-ERD undergoing functional endoscopic surgery (FES), followed by ASA desensitization and maintenance treatment, being the first prospective cohort study carried out in Chile. Methods: One-year follow-up of 12 patients with N-ERD treated with FES, desensitization and maintenance with ASA. In each control, medication score, sinonasal symptomatology (SNOT-22), PEF (peak expiratory flow), nasal polyposis (Lildholdt score) and appearance of adverse effects were recorded. Paranasal cavities computed tomography (CT) was performed at baseline and at 12-month follow-up to calculate Lund-Mackay score. Results: Patients presented a reduction of SNOT-22 after the FES maintained at 12 months (p=0.002), the symptoms with the greatest reduction were feeling embarrassed and nasal obstruction. Lildholdt score was also significantly reduced (p=0.001), in only three patients the nasal polyps recurred and all were small. The PEF showed a slight non-significant increase of 3.3%. 75% of patients had an adverse effect, the most frequent being abdominal pain (66.7%), but none of the 12 patients required discontinuation of aspirin treatment in 1 year follow-up. The Lund-Mackay score had a significant reduction of 6.6 points (p<0.001). Conclusion: ASA desensitization is safe and effective in reducing upper and lower respiratory symptoms in patients with N-ERD, delays the reappearance of nasal polyps, although it is not exempt from adverse effects, the vast majority being mild.